Cognitive constraints on optimal foraging in frog-eating bats. (September 2018) - Hemingway, Claire T.; Ryan, Michael J.; Page, Rachel A.
Abstract : Animals are expected to optimize energy intake when choosing between different foraging options. A common explanation for deviations from optimal economic decisions is that there is an imperfect relationship between physical reality and an animal's perceptual processes, which can constrain assessment of profitability. One such phenomenon that is apparently ubiquitous across taxa is proportional processing, where a perceived change in a stimulus is proportional to the change in stimulus magnitude. In this study, we investigated whether proportional processing explains how frog-eating bats, Trachops cirrhosus, discriminate between patches of frog choruses that vary in their number of calling frogs. To test this, we created artificial choruses consisting of one to six calling frogs. In the flight cage, we then tested the preference of bats ( N = 17) with every pairwise combination of chorus size. We found that while bats generally preferred larger choruses, preferences for larger choruses were better explained by the relative, not absolute, differences in chorus sizes. This indicates that T. cirrhosus is perceptually limited in its ability to discriminate between choruses of varying size as the choruses increase in size. Foragers are likely to be less choosy when choosing among larger patches. Highlights: We investigated perceptual limitations in patch size assessment in frog-eating bats. Frog-eating bats preferred larger choruses, with more calling frogs. Bats attended to relative, not absolute, differences when choosing larger chorus sizes.